Pengaruh Manajemen Laba dan Rasio Aktivitas Terhadap Peringkat Obligasi pada Perusahaan Sektor Property, Real Estate dan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Juhari, Dalvad; Nelvirita, Nelvirita (Universitas Negeri Padang, 2025)
This study examines how activity ratios and earnings management effect bond ratings. The study sample includes infrastructure, real estate, and property companies listed on the Indonesia Stock Exchange between 2019 and 2023. The companies were chosen using purposeful testing. This study uses IDX's yearly report. Multiple regression analysis examines data. This study reveals that earnings management does not affect bond ratings but the activity ratio does.